Halophytic Plants for Animal Feed - Attia-Ismail, Salah Abdelaty (Bentham Science Publishers, 2022)
Halophytic plants are a fascinating group of plants that also serve as dietary feed for livestock. Their utilization is essential for sustainable agriculture and maintaining ecological balance. This book explains the nature of halophytic plants through an in-depth presentation of their botanical and nutritional characteristics. Chapters of the book highlight different aspects of halophytes on a botanical, histological, ecological and nutritional basis when utilized as animal feed components. The issues of the histo-chemical aspects of halophytes are addressed with regard to their impact on nut.